Subjective and confirmatory personal introspections of cultural city holidays. Issue 4 (5th October 2015) - Gountas, John; Gountas, Sandra
Abstract : Purpose: – This paper aims to explore tourism consumer's perceptions of cultural, emotional and behavioural differences. The subjective personal introspection (SPI) approach is used to investigate specific cultural differences which impact tourism satisfaction. It aims to identify the key attributes of cultural tourism satisfaction by comparing three European cities. The cultural attributes are synthesised into a confirmatory personal introspection (CPI), and a provisional research model is proposed. Design/methodology/approach: – The research data of the cultural experiences are based on SPI data of "native-visitors" to London and ordinary visitors to Venice and Barcelona. The duration and the travel arrangements are the same for all three cultural experiences. The CPI uses thought experiments to formulate new research propositions. Findings: – The SPI results show that the tourism gaze focus can be the cognitive-affective experiences of cultural holidays. Tourism consumer satisfaction is dependent on the quality of natural and man-made attractions and the social-emotional interactions between the hosts and guests in a destination. The three cities in our research, London, Venice and Barcelona, have different micro-cultures and levels of social-emotional interactions vary considerably between them. Overall tourism satisfaction is hypothesised to be influenced by the degree of social interaction and micro-cultural differences. Practical implications: – The findings support the usefulness of SPI in tourism consumer research. SPI research findings produce in-depth understandings of the cultural tourism product attributes which cannot be captured in any other way. The personal insights are valuable to marketing professionals because they provide first-hand feedback of consumer's perceptions over a longer period than a focus group session. The confirmatory introspections are valuable hypotheses to be tested empirically with specific tourism segments to identify product strengths and weaknesses as well as opportunities and threats. Originality/value: – The use of SPI and CPI produces original hypotheses of the cultural tourism attributes which influence tourism satisfaction. The paper demonstrates that the tourism gaze can be expanded to investigate the cognitive-affective observations which have a direct effect on tourism satisfaction and decision-making.